PENERAPAN METODE INTERAKTIF UNTUK MENINGKATKAN KEAKTIFAN SISWA PADA PEMBELAJARAN ONLINE - Siska Wahyuni Damanik; Jacob Stevy Seleky (UPT Penerbitan Universitas Jember, 2022)
Effective learning is a learning process that actively engages students. Student activity is one of the indicators of the achievement of an effective learning process. In addition, a teacher is expected to be able to apply the right methods in increasing student activity. When the author teaches in a class, it is found that some students have not shown their activeness during online learning. Regarding this issue, the writing of this article aims to examine the application of interactive methods in increasing student activity in the online learning. The research method used is descriptive qualitative. This method is carried out by revealing phenomena, variables, and facts that occur during the research. The online learning is carried out using the team’s application by utilizing all its supporting features to apply the interact method. The result obtained is that the application of interactive methods during online learning can increase student activity. Thus it can be concluded that the application of interactive methods can increase student activity during online learning Keywords: Interactive methods, online learning, student’s activeness